Soil mechanics and foundations - Budhu, Muni (John Wiley, 2007)
Introduction to soil mechanics and foundations - Geological characteristics of soils and sils investigation - Physical soil parameters - One-dimensional flow of water through soils - Stresses, strains and elastic deformations of soils - One -dimensional consolidation settlement of fine-grained soils -Shear strength of soils - A critical state model to interpret soil behavior - Bearing of capacity of soils and settlement of shallow foundations - Pile foundations - Two-dimensional flow of water through soils - Stability of earth retaining structures - Slope stability - Appendices.